Effectiveness of Reproductive Health Education Using the Health Belief Model (HBM) Approach to Increasing Reproductive Health Knowledge of Adolescents - Herlina, Herlina; Virgia, Vera (Universitas Islam Lamongan, 2024)
Adolescence is a stage of potential and vulnerable psychological development, known as the phase of searching for identity, because in this phase they can no longer be said to be children but also cannot be said to be adults, and also in this phase teenagers are not yet able to master and maximize physical and psychological functions. This research is a quantitative research using a quasi-experimental method with a two group pre-test post-test design. The population of this study were all class IX students of Mojoanyar Middle School with a sample of 90 respondents who were divided into intervention groups and control groups and the sampling method used purposive sampling. From this research, it was found that there was an increase in health education knowledge using the health belief model (HBM) approach in the intervention group and control group. This Health Belief model (HBM) uses several indicators, namely, vulnerability, seriousness, benefits, obstacles and self-confidence. The results of the p value in this research are about increasing adolescent reproductive knowledge regarding vulnerability (p=0.000), seriousness (p=0.000), benefits (p= 0.000), obstacles (p= 0.000), and self-confidence (p= 0.000). Thus, it was found that there was an increase in adolescent reproductive health knowledge through health education using the health belief model (HBM) approach.